2015
DOI: 10.1183/13993003.01537-2014
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in idiopathic pulmonary fibrosis with mild-to-moderate restriction

Abstract: The clinical course of pulmonary hypertension (PH) in idiopathic pulmonary fibrosis (IPF) is not known except in advanced disease.488 subjects in a placebo-controlled study of ambrisentan in IPF with mild-moderate restriction in lung volume, underwent right heart catheterisation (RHC) at baseline and 117 subjects (24%) had repeated haemodynamic measurements at 48 weeks.The subjects were categorised into a) World Health Organization (WHO) Group 3 PH (PH associated with pulmonary disease), n=68 (14%); b) WHO Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
127
1
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(149 citation statements)
references
References 16 publications
3
127
1
18
Order By: Relevance
“…Patients with PH and normal capillary wedge pressure had lower DLCO and increased haemoglobin desaturation at exercise. Interestingly, PH does not seem to progress rapidly in these patients, as repeat catheterisation at 48 weeks yielded levels quite similar to baseline [87].…”
Section: Alterations In Pulmonary Haemodynamicsmentioning
confidence: 93%
See 2 more Smart Citations
“…Patients with PH and normal capillary wedge pressure had lower DLCO and increased haemoglobin desaturation at exercise. Interestingly, PH does not seem to progress rapidly in these patients, as repeat catheterisation at 48 weeks yielded levels quite similar to baseline [87].…”
Section: Alterations In Pulmonary Haemodynamicsmentioning
confidence: 93%
“…There is no correlation between mPAP and operating lung volumes [87,91]. Anatomical-functional correlation analysis in 26 explanted lungs showed that mPAP is significantly correlated with the extent of fibrosis in damaged regions, but no correlation exists between mPAP and the extent of venous lesions in less-damaged areas [28].…”
Section: Alterations In Pulmonary Haemodynamicsmentioning
confidence: 94%
See 1 more Smart Citation
“…Much less is known about the natural cause of pulmonary hypertension in idiopathic pulmonary fibrosis (IPF), because most studies are limited by their focus on advanced lung disease. Recently, RAGHU et al [33] filled this gap using right heart catheterisation data from 488 subjects enrolled in a placebo-controlled study of ambrisentan in IPF with mild-moderate lung volume restriction. As in COPD, it was shown that severe pulmonary hypertension is rare in IPF and that pulmonary artery pressure remains stable over a 1-year period in the majority of IPF patients.…”
Section: Pulmonary Hypertension Secondary To Pulmonary Diseasementioning
confidence: 99%
“…IPF clinical trials using vasodilators such as the endothelin receptor antagonists have thus far been negative [14][15][16]. It appears, however, that sildenafil has pleiotropic properties beyond its traditional vasodilatory effects that may render it especially attractive as an add-on treatment for IPF.…”
mentioning
confidence: 99%